Data protection as privilege—Factors to increase meaning of GDPR in vulnerable groups - Breuer, Jonas; Heyman, Rob; Brakel, Rosamunde van (Frontiers in Sustainable Cities, 2022)
The General Data Protection Regulation in the EU has the potential to empower citizens towards data-based innovation, for example in so-called smart cities. Realising this potential in practice is challenging, mainly because not everyone has the capabilities or data litercacy, seemingly expected by the lawmakers, to make use of relevant legal provisions. This empirical study therefore sets out to investigate what can increase capabilities of urban dwellers to understand and exercise their rights to data protection, as means to increase participation in smart city socio-technical systems. We concentrate on vulnerable groups and criticise the GDPR and data literacy conceptualisations as regarding literacies as intrinsic life goals instead of instrumental means. We expand vulnerability to capability deprivation, to overcome solely negative associations of vulnerability and provide a more constructive framing in support of literacies of everyone, including less literate or more vulnerable, based on a dynamic understanding of layered vulnerabilities. Based on this approach, we consider what is lacking to achieve GDPR literacy. In order to do so, we conducted interviews with representatives of civil society organisations supporting different groups in Flanders, Belgium. Based on these insights, we argue that a layered approach to vulnerability leads to a layered approach to capabilities, and then, to a layered approach of support based on the most appropriate conversion factors for different groups.